Watery diarrhea between Vibrio cholera and Aeromonas hydrophila during Iraqi cholera outbreaks: Diare berair antara Vibrio cholera dan Aeromonas hydrophila selama wabah kolera di Irak - Aghadeer Sarmad Najeeb; Musaab Ahmed Ibrahim; Hala Luay Abduljabbar (Universitas Muhammadiyah Sidoarjo, 2024)
Cholera remains a significant health challenge globally, especially in regions with poor infrastructure and healthcare. This study aimed to detect Aeromonas hydrophila in clinical samples from diarrhea patients during the 2022-2023 outbreaks in Iraq. Archived samples from Baquba General Teaching Hospital were analyzed using culture media, biochemical tests, and the VITEK 2 system. Both Vibrio cholerae and A. hydrophila isolates produced virulence factors such as hemolysin, protease, lipase, phospholipase, and biofilm. Antibiotic susceptibility testing showed A. hydrophila was susceptible to cefepime, ceftazidime, amikacin, imipenem, meropenem, and piperacillin-tazobactam but resistant to aztreonam, levofloxacin, and ciprofloxacin. V. cholerae was susceptible to amikacin, imipenem, meropenem, piperacillin-tazobactam, doxycycline, and chloramphenicol but resistant to trimethoprim-sulfamethoxazole and ampicillin. The findings highlight the need for better recognition of Aeromonas as a gastrointestinal pathogen and emphasize the importance of improved diagnostics and public health initiatives to reduce diarrheal diseases. Highlight: Detection Methods: Culture media, biochemical tests, VITEK 2 system used. Virulence Factors: Hemolysin, protease, lipase, phospholipase, biofilm production identified. Antibiotic Resistance: Specific resistance observed in A. hydrophila and V. cholerae. Keyword: Cholera, Aeromonas hydrophila, Antibiotic Susceptibility, Diarrhea, Iraq Outbreak